Isolated Vanadium Surface Complexes on Aluminum Fluoride ‐ A Model for the Relevance of Oxygen Atoms of Aluminum Oxide Supports in Catalytic Oxidation Reactions. Issue 11 (5th August 2013) - Haeßner, Carmen; Müller, Barbara; Storcheva, Oksana; Köhler, Klaus
Abstract The redox properties and reactivity of oxidation catalysts of isolated mononuclear oxovanadium complexes supported on aluminum fluoride, AlF3, and on aluminum oxide, Al2O3, were compared. AlF3 is an interesting model for a non‐oxide support to study the role of oxygen atoms of nonreducible oxide supports during catalytic oxidation with supported vanadium oxide catalysts. Solid‐state 1H NMR indicate the presence of reactive FH and OH groups on the surface of AlF3 and the presence of reactive OH groups on the surface of Al2O3. Oxovanadium(V) triisopropoxide, VO(OiPr)3, was grafted onto the surfaces of both supports. Immobilization led to mononuclear vanadium complexes with oxidation states of +V (major) and +IV (minor). In contrast to alumina, the vanadium surface species were neither reducible nor oxidizable on AlF3. Redox cycles were studied by electron paramagnetic resonance of vanadium(IV). In situ IR spectroscopic investigations showed high and comparable initial stoichiometric reactivity to propane for both catalysts. Reactions on AlF3 stopped after a short initial period as a result of the absence of surface oxygen of the support. The results indicate the relevance of surface oxygen of the alumina support in oxidation reactions. In contrast to vanadium on alumina, VOx/AlF3 is catalytically inactive in the oxidative dehydrogenation of propane. Only after partial oxidation of AlF3 to Al2O3 above 500 °C was catalytic activity observed. The investigations support a recent report contradicting common oxygen‐exchange models, which assume the involvement of only surface vanadium oxide layers, and thus it appears as though a more complex process is in operation.